Fatigue of cable anchorages on a cable-stayed bridge - Nor Ashikin, Muhamad Khairussaleh (2016)
Studies have shown that the connection details used for cable anchorage blocks on cablestayed bridges have the potential for fatigue damage due to fluctuating stresses generated by the cyclic traffic loads passing over the bridge. To investigate the fatigue damage and determine the remaining fatigue life of a cable anchorage block used on a cable-stayed bridge, finite element (FE) analyses were undertaken by using the Fatigue Load Model 4 (FLM 4) proposed by the Eurocodes to identify the most fatigue-critical locations within the details.